3D Organic–Inorganic Perovskite Ferroelastic Materials with Two Ferroelastic Phases: [Et3P(CH2)2F][Mn(dca)3] and [Et3P(CH2)2Cl][Mn(dca)3]1. Issue 25 (10th April 2019) - Zhao, Meng‐Meng; Zhou, Lin; Shi, Ping‐Ping; Zheng, Xuan; Chen, Xiao‐Gang; Gao, Ji‐Xing; He, Lei; Ye, Qiong; Liu, Cai‐Ming; Fu, Da‐Wei
Abstract: Organic–inorganic hybrid perovskite‐type multiferroics have attracted considerable research interest owing to their fundamental scientific significance and promising technological applications in sensors and multiple‐state memories. The recent achievements with divalent metal dicyanamide compounds revealed such malleable frameworks as a unique platform for developing novel functional materials. Herein, two 3D organic–inorganic hybrid perovskites [Et3 P(CH2 )2 F][Mn(dca)3 ] (1 ) and [Et3 P(CH2 )2 Cl][Mn(dca)3 ] (2 ) (dca=dicyanamide, N(CN)2 − ) are presented. Accompanying the sequential phase transitions, they display a broad range of intriguing physical properties, including above room temperature ferroelastic behavior, switchable dielectricity, and low‐temperature antiferromagnetic ordering ( T c =2.4 K for both1 and2 ). It is also worth noting that the spontaneous strain value of1 is far beyond that of2 in the first ferroelastic phase, as a result of the precise halogen substitution. From the point view of molecular design, this work should inspire further exploration of multifunctional molecular materials with desirable properties. Abstract : Ferroelastic behavior : By using halogen substitution, two 3D organic–inorganic hybrid perovskite‐type materials [Et3 P(CH2 )2 F][Mn(dca)3 ] (1 ) and [Et3 P(CH2 )2 Cl][Mn(dca)3 ] (2 ) (dca=dicyanamide, N(CN)2 −, see figure) are reported. These materials display a broad range of intriguing physical properties, including above room temperature ferroelastic behavior, switchable dielectricity, and low‐temperature antiferromagnetic ordering.